Pragmatics Analysis on Anger Expression in #IndonesiaTerserah on Twitter - Ulrikayanti, Gabey Faustena (Indonesian Journal of English Language Studies (IJELS), 2022)
This study attempts to identify the intention and pragmalinguistic forms of anger expression in tweets using #IndonesiaTerserah on November 15th, 2020. A corpus of 30 tweets is analyzed within pragmatic analysis framework. In analyzing the data, the illocutionary acts and pragmalinguistics forms of the tweets are the focus. The interpretation entails the analysis of text, addressing, and the identification of connotative meanings. The data are collected using Twitter Archiver Programme (API). An underlying assumption for choosing the time frame is the hashtag reached the highest trending in Indonesia as response to two mass gathering incidents in Soekarno Hatta airport on 10 November 2020, and Petamburan on 14 November 2020. Based on the findings of illocutionary act, the intention of using #IndonesiaTerserah in the tweets mostly is to state the fact and elaborate their opinions regarding the issues. The irritated feeling dominates the intention of using #IndonesiaTerserah. However, they also express expectation to the stakeholders to handle the issues in a better way. Based on the findings on pragmalinguistics forms, anger is expressed in thinly veiled form of cynical humor in order to make their message more straightforward to the addressees.